The Influence of Perceived Risk toward Online Purchase Intention (Case Study: Students of Bengkalis State Polytechnic) - Sur Yani (Politeknik Negeri Bengkalis, 2021)
In this globalization era business competition cannot be avoided. As a result, competition arises in offering quality products at prices that are able to compete in the market. The current phenomenon that is interesting among young people is online shopping. Online shopping is an online trading activity or transaction that takes into account the ease, convenience, conformity and the price offered to consumers as well as the risks that can arise when shopping online. The purpose of this research is to study and try to investigate and also clarify how consumer students of Bengkalis State Polytechnic perceived risk toward online purchase intention.The results obtained have shown that all the formulated hypothesis is proven to have positive and significant influence. Based in hypothesis testing which is conducted, showing that there is a influence between the perceived risk toward online purchase intention. Based on the results of the study showed that the calculated value of each independent variable is 8.652 for perceived risk, while the value of t table is 1.984467 (t count > t table) means that the perceived risk variable significantly influences the online purchase intention. While the results of the analysis of the coefficient of determination obtained a value of 0.441 or 44.1%, which means the effect of the independent variable (perceived risk) on the dependent variable (online purchase intention) of 0.441, this shows that the contribution of the independent variables amounted to 44.1% while the remaining 55.9% is influenced by other factors not examined in this study.